THE STRATEGY OF PRINCIPALS IN DEVELOPING THE SCHOOL QUALITY: A CASE STUDY AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Ghofur, M Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Schools Quality is the hope and demand of all education partners. Everyone wants to find information in organizations that have great quality. Because of this, schools or educational organizations should have the option to offer great support and quality so as not to give up and be ready to compete with other schools. This study aims to illustrate the principal's strategy in developing the quality of Islamic elementary schools in Integrated Islamic Elementary School of Iqro Karangploso Malang. This type of research uses qualitative methods. Data were collected through observation, interviews, and documentation. The results of this study indicate that the principal's strategy in developing the quality of education includes 1) formulating a plan with a vision, short-term mission, and medium-term goals (4 years); 2) implementing strategies by increasing discipline, increasing student's national exam results, conducting extracurricular activities, establishing cooperation with the community.Keywords: Principal Strategy; Quality; Education.